ESTIMATION OF GENETIC DIVERSITY IN FARMERS’ VARIETIES OF RICE (Oryza sativa L.) THROUGH DUS DESCRIPTORS - U. CHAITANYA and P. ARUNA SRI YADAV, L.V. SUBBA RAO, M. CHIRANJEEVI K. LAVANYA, C. PADMA, R. SURENDER (The Journal of Research, PJTSAU, 2017)
The genetic divergence in 57 Farmers’ Varieties from the eastern region of the country was estimated using Mahalnobis’s D2 – statistics. Cluster analysis was done based on morphological characteristics. The genotypes were grouped into 12 clusters, of which cluster I, III, II were the major clusters. A total of 33 genotypes were grouped in cluster I, followed by cluster III and II with 8 and 5 genotypes respectively. Cluster III showed maximum intra cluster divergence while inter cluster divergence was maximum between clusters IX and X. Traits viz., Gelatinization temperature, Grain Aroma, Endosperm content of Amylose,Presence of amylose and Decorticated grain colour were the major contributors to genetic divergence. The study helped to understand the extent of genetic diversity among the Farmers’ varieties which are a potential source that can be exploited.